Systematics and spatio-temporal evolutionary patterns of the flavopilosa group of Drosophila (Diptera, Drosophilidae) - Antoniolli, Henrique R.m.; Carvalho, Tuane L.; Gottschalk, Marco S.; Loreto, Elgion L.s.; Robe, Lizandra J.; Deprá, Maríndia (Zootaxa, 2024)
The Drosophila flavopilosa group comprises morphologically cryptic species that are ecologically restricted to feeding, breeding and ovipositing on flowers of Cestrum and Sessea (Solanaceae). Previous studies confirmed the monophyly of the group and the success of DNA barcoding in identifying a subset of its species, but several others remain yet to be evaluated. Furthemore, the taxonomy of the group remains incomplete, with only nine of the 17 species assigned to subgroups. Here, we accessed the phylogenetic relationships and spatio-temporal evolutionary patterns of the flavopilosa group based on a mitochondrial and two nuclear genes, providing the first molecular support to the subdivision of the group and suggesting a new taxonomic scheme for its species. Barcoding proved to be an effective tool, as all species were reciprocally monophyletic and different analyses of species delimitation yielded congruent results. The close relationship of D. flavopilosa with D. cestri and D. cordeiroi was strongly supported, suggesting that the latter should be placed in the flavopilosa subgroup together with the first. Furthermore, D. mariaehelenae was positioned as sister to D. incompta, supporting its inclusion in the nesiota subgroup. Despite new taxonomic assignments, the synapomorphic status of the diagnostic characters proposed for both subgroups was supported. Based on them, each of the remaining species were placed into one of both subgroups. Divergence time estimates suggest that their diversification coincided with the divergence of Sessea and Cestrum, providing an interesting case of coevolution.